2020
DOI: 10.3389/fmed.2020.564764
|View full text |Cite
|
Sign up to set email alerts
|

Experience With Medical Treatment of Cesarean Scar Ectopic Pregnancy (CSEP) With Local Ultrasound-Guided Injection of Methotrexate

Abstract: Objective: Ectopic pregnancy within Cesarean section scars is a rare condition. Late diagnosis carries significant risk of bleeding with poor prognosis for survival. There is no consensus on the management of this type of pregnancy. Historically, our facility offered an intra-muscular injection of methotrexate that resulted in a significant failure rate and later need for surgery. We hypothesized that injecting methotrexate directly into the gestational sac would improve the success rate of the treatment.Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…MRT is helpful in distinguishing cervical ectopic from scar ectopic pregnancy or consideration for expectant management of cesarean scar ectopic pregnancy. 6 Here, the case highlights the importance of early diagnosis and management of cesarean scar ectopic pregnancy. This patients presentation was similar to other case reports found in literature.…”
Section: Discussionmentioning
confidence: 96%
“…MRT is helpful in distinguishing cervical ectopic from scar ectopic pregnancy or consideration for expectant management of cesarean scar ectopic pregnancy. 6 Here, the case highlights the importance of early diagnosis and management of cesarean scar ectopic pregnancy. This patients presentation was similar to other case reports found in literature.…”
Section: Discussionmentioning
confidence: 96%
“…The advantages of local intragestational methotrexate to treat CSP has been previously described (19,20). However, the medical treatment alone of intragestational methotrexate remains controversial (13,21). A previous study reported that a local combined with systemic methotrexate without D&C has a success rate of 80.9% (22).…”
Section: Discussionmentioning
confidence: 98%
“…The use of local ultrasound-guided injection of MTX into the gestational sac was considered as a well tolerated and effective therapeutic treatment for CSP, when performed by a trained team on a haemodynamically stable patient in the early stages of CSP. It was showed by a study of Gerday et al on a case series of nine patients [19].…”
Section: Medical Managementmentioning
confidence: 88%